The effect of aerobic training according to genetic diversity on some biochemical variables and the digital level to reduce sports injuries in swimming - Hameed Kzar, Fatimah (International Journal of Psychosocial Rehabilitation, 2020)
Analysis of the condition of the students (research sample) shows a genetic diversity of ACE I/D, with a 75% frequency of ACE DD, followed by the ACE ID gene isotope by 25%. The aerobic training program has a positive effect on the biochemical variables under consideration, where there were statistically significant differences between the tribal and dimensional measurements in favor of dimensional measurement. Students who have an ACE ID gene respond to aerobic training more than female students who have an ACE DD gene. To emphasize the knowledge of ACE I/D genetic diversity for young people as they approach practice to discover the potential that well-founded training can transform into effective capabilities. Selection of female students in sports and aerobic games is based on the ACE ID gene pattern. Conduct such research on larger and more diverse samples in the field of sports with various collective and individual activities. Study different types of genes nominated to influence physical performance Candidate genes, which may have an effective effect on the development of physical performance and thus may enable us to develop a model for selecting players for different activities in order to achieve the required level of achievement by selecting promising elements.